2013
DOI: 10.1111/jpn.12043
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Saccharomyces cerevisiae supplementation on apparent total tract digestibility of nutrients and fermentation profile in healthy horses

Abstract: SummarySupplementation with Saccharomyces cerevisiae (SC) in horses may have some potential to modify microbial populations and thereby improve fibre digestibility. The aim of this study was to investigate the effects of SC on apparent total tract digestibility (ATTD) of nutrients, with a special focus on fibre digestion in healthy horses. The fermentation profile of microbial populations was another focus of interest. Twelve geldings were randomly assigned to three groups. The basal diet consisted of cracked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 22 publications
(58 reference statements)
0
7
0
5
Order By: Relevance
“…In equine studies, in vivo evaluation of nutritional solution effects on the hindgut microbiota was performed either by studying directly caecum or colon content using fistulated horses (8,9,14,15) , or, more frequently, using faeces, which is non-invasive and less labour-intensive (16)(17)(18)(19)(20)(21)(22) . However, to our knowledge, no study has ever verified that changes observed in the faeces under supplementation were consistent with those in the hindgut microbial ecosystem.…”
mentioning
confidence: 99%
“…In equine studies, in vivo evaluation of nutritional solution effects on the hindgut microbiota was performed either by studying directly caecum or colon content using fistulated horses (8,9,14,15) , or, more frequently, using faeces, which is non-invasive and less labour-intensive (16)(17)(18)(19)(20)(21)(22) . However, to our knowledge, no study has ever verified that changes observed in the faeces under supplementation were consistent with those in the hindgut microbial ecosystem.…”
mentioning
confidence: 99%
“…Dabei ergab sich eine Abnahme der SC-Konzentration vom Zäkum (4,4 x 10 6 KBE/ml) zum Kolon (5,6 x 10 4 KBE/ml) um zwei Zehnerpotenzen [39]. Im Kot ließen sich bei Gabe von SC lediglich 220 ± 283 KBE/g isolieren statt der erwarteten 1,1 x 10 6 ± 1,7 x 10 5 KBE/g unter der Bedingung, dass SC weder verdaut noch kolonisiert wird [48].…”
Section: Einsatz Von Saccharomyces Cerevisiaeunclassified
“…Diese Daten deuten darauf hin, dass SC vermutlich das saure Magenmilieu überlebt und an seinen Wirkungsort im Dickdarm gelangen kann. Dort findet jedoch wahrscheinlich keine Ansiedlung dieser Hefen statt, sondern ihre Konzentration nimmt aufgrund von Fermentationsprozessen durch die wirtseigene Mikrobiota im Verlauf des Dickdarms sukzessive ab [48].…”
Section: Einsatz Von Saccharomyces Cerevisiaeunclassified
“…Die Detektion der Toxine A und B über Immunassays, zellzytotoxische Assays oder eine PCR, zum Nachweis der für die Toxinbildung verantwortlichen Gene des Bakteriums, stellen sensitivere Methoden dar (Jones 2000, Weese et al 2000, Jones 1989). (Mackenthun et al 2013). …”
Section: Introductionunclassified